Self-Efficacy: Implications for Organizational Behavior and Human Resource Management - Gist, Marilyn E. (Academy of Management Review, 1987)
Self-efficacy (one's belief in one's capability to perform a task) affects task effort, persistence, expressed interest, and the level of goal difficulty selected for performance. Despite this, lit...